Safety assessment of maize grain attained from nano-copper treated seeds on chickens - Xuan, Nguyen Thi; Trang, Do Thi; Thu Hien, Le Thi (Vietnam Journal of Biotechnology, 2018)
Metal nanoparticles used as micronutrient fertilizers in cultivation to improve both the quality and the quantity of the crop have been extensively utilized. The application of these nano-formulations for animal feed needs to be determined the biosafety to the health of humans or animals. In this study, maize seeds were treated with nanoparticle copper (nCu) (20 mg/kg and 1000 mg/kg dry weight (DW)) and their grain productions were used for chicken feed. After treatment, the chickens were monitored the survival rate and changes in body weight (BW) gain and finally were sacrified to determine morphology and/or function of systemic organs including liver, kidney and some others as well as analyze the mineral contents in the muscle tissues. As a result, the serum levels of ALT, AST and creatinine were not significantly different among the treatment groups as compared to the control group (p  0 05). In addition, the BW gain, the weight and morphology of the organs including liver, kidneys, heart, lungs and gastrointestinal tract were within normal limits and no significant difference among the groups was observed. However, the BW gains of the chickens, which were fed with maize grains attained from 1000 mg/kg DW nCu-treated seeds, tended to be less than that of the control chickens. Therefore, maize grains derived from 20 mg/kg DW nCu-treated seeds are safe to feed chickens.